Spatial Distribution and Gastropod Associations Based on Tawiri and Tanjung Tiram Mangrove Habitat in Ambon, Maluku, Indonesia - Simatupang, Candida Putri Nauli; Bengen, Dietriech G.; Retraubun, Alex S.W.; Ismet, Meutia Samira; Abrahamsz, Jodie G. (Universitas Diponegoro, 2025)
Ambon Island is an area that has the potential for a mangrove ecosystem. Ambon Island has a unique bay covered with mangroves. When viewed from the topography, Ambon Bay is divided into Outer Ambon Bay and Inner Ambon Bay, which are separated by a narrow and shallow threshold. Tawiri has five species of mangroves, and Tanjung Tiram has three species of mangroves. The density of mangroves as the main constituent of the ecosystem greatly influences the existence of associated biota, namely gastropods themselves. Gastropods have an important role in the food chain cycle in the mangrove ecosystem. This research was conducted in August–September 2023 in the Tawiri (Outer Ambon Bay) and Tanjung Tiram (Inner Ambon Bay) mangrove areas. Data collection for gastropods and mangrove ecosystems used quadrat transects, while for organic materials they used sediment cores. The association between gastropods and mangroves was analyzed using correspondence analysis (CA). The research results show that Tawiri has seven families and 10 species of gastropods. Tanjung Tiram has 3 families and 5 species of gastropods. Gastropod species at both study locations were divided into three different size classes for each location. Gastropods at each research location were found to be closely associated with mangroves because mangroves provide sufficient food sources for gastropod life. The results of this research can be useful for providing the latest data regarding the distribution of gastropods and mangroves in Tawiri and Tanjung Tiram.